SYNTHESIS OF A DEVICE FOR REMOTE CONTROL OF A VIDEO CAMERA USING THE LANC PROTOCOL - Semenov, А. О.; Stalchenko, О. V.; Voitsekhovska, О. О.; Khloba, А. А.; Krystoforov, A. V. (Systems and Technologies, 2023)
The expediency of using video camera remote control devices when using auxiliary video equipment is proven by the ever-increasing level of complexity and improvement of modern video shooting technologies. Companies producing systems for remote control of video equipment offer control systems with wireless radio interfaces for high-budget projects. But the price of such an interface can exceed the cost of a high-budget professional video camera. In most cases, management interfaces differ from manufacturer to manufacturer and are implemented based on leading wired management protocols. The use of these protocols is largely due to the need to implement very high-speed information transmission and its strict synchronization with the frame pulse generator of the video camera, which in turn provides control of entire groups of objects with high speed and fairly accurate synchronization in time, as well as wired information transmission lines are more secure and reliable. The object of research in the work is the widespread LANC protocol (CONTROL-L), which is used by two-way data exchange systems and is necessary for the remote control of video cameras. The paper proposes a device based on this protocol that allows remote control of the camera (data exchange takes place via cable). For this, an overview of existing video camera control devices was conducted. The analysis of the LANC protocol was carried out, and its working principle was considered. The protocol allows you to use 14 steps of changing the zoom speed (7 speeds in the direction of increasing the image and 7 speeds in the direction of reducing the image), so for an almost smooth gradual increase or decrease in the speed of the zoom; it is advisable to use not discrete buttons, but an analog variable resistor-joystick. The proposed electric circuit of the video camera remote control device is based on the Microchip microcontroller – PIC16F84. Modern microcontrollers have low consumption currents, so it becomes possible to use the power supply line of external devices built into the LANC connector to power the remote control controller, which allows you to connect a load with a current of up to 100 mA. The operation of the device was checked during the simulation. The correct operation of the algorithm for converting the resistance of the “joystick” resistor of the zoom into the command code has been confirmed. The given oscillograms are obtained from the device layout. The obtained results confirm the protocol’s theory and the device’s correct functioning.